Circular Economy and Sustainability: Concepts, Perspectives, and (Dis)Agreements - Costa, Berta José (2021)
In the last decades, the concern over natural resources, sustainability, and the current linear economic model based on continuous growth is one of the great challenges of our time. The assumption that there is an unlimited supply of natural resources and that the environment has an unlimited capacity to absorb waste and pollution is no longer a current trend, and growing attention has been paid to it worldwide. This chapter represents a contribution to the continuous conceptual development of circular economy and sustainability, and it also reviews how these two concepts have evolved over the past decades. An extensive literature review was conducted, employing bibliometric analysis to scrutinise the state of the art, the perspectives, the agreements and disagreements among these concepts and their correlation.